Polarization invariant plasmonic nanostructures for sensing applications - Landobasa Y. M. Tobing (Nature Portfolio, 2017)
Abstract Optics-based sensing platform working under unpolarized light illumination is of practical importance in the sensing applications. For this reason, sensing platforms based on localized surface plasmons are preferred to their integrated optics counterparts for their simple mode excitation and inexpensive implementation. However, their optical response under unpolarized light excitation is typically weak due to their strong polarization dependence. Herein, the role of rotational symmetry for realizing robust sensing platform exhibiting strong optical contrast and high sensitivity is explored. Specifically, gammadion and star-shaped gold nanostructures with different internal and external rotational symmetries are fabricated and studied in detail, from which their mode characteristics are demonstrated as superposition of their constituent longitudinal plasmons that are in conductive coupling with each other. We demonstrate that introducing and increasing internal rotational symmetry would lead to the enhancement in optical contrast up to ~3x under unpolarized light illumination. Finally, we compare the sensing performances of rotationally symmetric gold nanostructures with a more rigorous figure-of-merit based on sensitivity, Q-factor, and spectral contrast.